Building Customer Loyalty: The Role of Customer Experience and Product Quality Among Skintific Users in Kolaka - Indah Febrianti; Andry Stepahnie Titing; Agus Zul Bay (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study explores the influence of customer experience and product quality on customer loyalty in the skincare industry, focusing on Skintific beauty product users in Kolaka Regency, Indonesia. The research adopts a quantitative approach, collecting data through a structured questionnaire distributed to respondents. The findings reveal that both customer experience and product quality significantly contribute to customer loyalty, with product quality having a slightly stronger impact. A positive brand experience enhances consumer engagement, but perceived product effectiveness and reliability remain key factors in fostering long-term loyalty. This study concludes that a strategic balance between experiential marketing and product innovation is crucial for maintaining customer retention. Future research is encouraged to examine additional factors such as brand reputation, pricing strategies, and social influence in shaping customer commitment.